2022
DOI: 10.1002/ccr3.5370
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identified a novel HIST1H1E heterozygous protein‐truncating variant in a 6‐month‐old male patient with Rahman syndrome: A case report

Abstract: Rahman syndrome is a rare autosomal-dominant intellectual disability syndrome caused by monoallelic pathogenic frameshift variants affecting the C-terminal domain (CTD) of the HIST1H1E gene. HIST1H1E is a single-exon, intronless gene located on chromosome 6p22.2. It encodes the linker histone H1.4, a member of the H1 histone family, and functions as a structural component of chromatin to control DNA compaction, gene expression regulation, DNA replication, recombination, and repair. The HIST1H1E protein contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There are reports of more than 20 types of frameshift (for example, at K173, K139, T142, K148, S150 and K157, etc.) mutations in human H1.4 subtypes from the patient’s samples that have been identified, which result in early truncation of CTD and the formation of a pathogenic variant of this protein with abnormal function that cause of Rahman syndrome [ 86 , 87 , 88 , 89 ]. The expression of an H1.4 CTD-truncated mutant in rat revealed the down-regulation of nearly 400 genes, and it has been found that many of these genes are involved in neuronal activities [ 86 ].…”
Section: Modulators Of Linker Histone Post-translational Modificationsmentioning
confidence: 99%
“…There are reports of more than 20 types of frameshift (for example, at K173, K139, T142, K148, S150 and K157, etc.) mutations in human H1.4 subtypes from the patient’s samples that have been identified, which result in early truncation of CTD and the formation of a pathogenic variant of this protein with abnormal function that cause of Rahman syndrome [ 86 , 87 , 88 , 89 ]. The expression of an H1.4 CTD-truncated mutant in rat revealed the down-regulation of nearly 400 genes, and it has been found that many of these genes are involved in neuronal activities [ 86 ].…”
Section: Modulators Of Linker Histone Post-translational Modificationsmentioning
confidence: 99%
“…A total of 23 frameshift variants from 52 patients (Burkardt et al, 2019;Ciolfi et al, 2020;Duffney et al, 2018;Flex et al, 2019;Helsmoortel et al, 2015;Indugula et al, 2022;Takenouchi et al, 2018;Tatton-Brown et al, 2017;Zhao et al, 2022) with neurodevelopmental disorders were curated from the large-scale genome-wide sequencing studies or individual patient reports or online databases and this study (Table 1; Figure 2). All are resulting in almost identical shorter proteins that contained a shared divergent C-terminal tail (Burkardt & Tatton-Brown, 2020;Flex et al, 2019).…”
Section: Mutation Pattern and Genotypephenotype Correlations For Hist...mentioning
confidence: 99%